THE EFFECT OF TAX MORALE AND TAXPAYER AWARENESS ON TAX COMPLIANCE WITH TAX LITERACY AS A MODERATING VARIABLE - Bariati, Siti Nuraeni; Kusumah, R Wedi Rusmawan (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This research intends to investigate and assess how tax morale and awareness among taxpayers influence tax compliance, with tax literacy acting as a variable that moderates this relationship. A quantitative methodology was utilized, with primary data gathered via questionnaires from 100 individual taxpayers who are registered at the Karawang Primary Tax Office. The sample was chosen using the Slovin formula and random sampling techniques. The data analysis was conducted using the Partial Least Square (PLS) method through SmartPLS 4 software. Findings show that tax morale significantly impacts tax compliance, whereas taxpayer awareness does not have a notable effect. Additionally, tax literacy does not serve as a moderating factor between tax morale or taxpayer awareness and tax compliance.